An investigation into the antecedents influencing unethical consumer behavior / Nazahah Abd Rahim … [et al.] - Abd Rahim, Nazahah; Abdul Jalil, Muna; Mohd Saad, Shakirah (2012)
This research investigates consumers’ motivation for behaving unethically and to understand the factors influencing it. It aims to develop a model predicting the factors or antecedents influencing unethical consumer behaviors. As there are less research and reports on this issue in Malaysia, thus study on this is important. Respondents from the Northern region of Malaysia were chosen as the sample for this study. A purposive sampling technique was implemented in selecting the respondents aged between 19 to 35 years old. The Theory of Planned Behavior (TPB) model is applied to reveal the secret behind it. It is found that the potential factors of consumers behaving unethically are attitude, subjective norms and perceived behavioral control. Given the complexity of this integrated model and simultaneous involvement of many factors, the SEM is used and a multivariate analysis technique is adopted. Results show that there are significant direct impacts among variables except for subjective norms. It is also found that there are mediating effects of intention in all relationships.